Participatory community analysis: Identifying and addressing challenges to Ethiopian smallholder livelihoods - Lunt, T.; Ellis-Jones, J.; Mekonnen, Kindu; Schulz, S.; Thorne, Peter J.; Schulte-Geldermann, Elmar; Sharma, K. (Informa UK Limited, 2018)
In 2012, Africa RISING conducted participatory community analysis (PCA) as the first phase of a participatory development approach in the Ethiopian highlands. The PCA identified trends, constraints, and opportunities – and shed light upon how farmers perceive livelihoods to be changing. Inputs, diseases, pests, soil fertility, post-harvest management, and fodder shortages were seen as challenges, while off-farm income has become increasingly important. Gender differences in livestock and crop preferences for food security and income sources were observed. PCA established development priorities in a way that researchers may have approached differently or missed, providing research development priorities for Africa RISING scientists.